Physical, physicochemical and sensory characteristics of cocoa beans (Theobroma cacao) variety FTA-4 harvested in the department of Arauca, evaluated under variable fermentation and drying conditions (2023)
The new varieties of cocoa, such as the FTA-4 clone from the department of Arauca - Colombia, have an incipient scientific review, so it could evaluate the behavior of the benefit of beans. In the fermentation phase, the residence time of the grain was analyzed (4 days or 6 days) and during the drying operation the behavior against natural solar drying and assisted convective drying was observed, the response variables that were analyzed physical as % of well-fermented grains, grain index, variables of a physicochemical nature such as % of fat,  of protein and total ashes, finally the sensory characteristics of flavor and aroma were evaluated allowed to generate the evaluation. An increased approval rate was obtained in grains that fermented for 6 days and whose drying was artificial (< 94% of well-fermented grains), in addition to the relationship between the factors is decisive to increase or decrease this parameter. The grain index was not significantly affected by the factors, it was constant at 1.96±0.013 g/grain. In the physicochemical section, statistical evidence was reported of the incidence of the type of drying and the fermentation time, in the concentration of both proteins and fat, being the best artificial drying for fermented cocoas for 4 days to increase the fat content (54.6 % w / w). The amount of cocoa bean protein increased in naturally dried beans from 6 days (11.51±0.071%) of fermentation without having a significant incidence of independent factors.  Through a sensory analysis it was possible to identify the profile of the FTA-4 cocoa of Arauca, and evaluated in the variations of the different factors identifying that naturally dried and fermented beans for 6 days I highlight in the panel highlight less sensation of acid and bitter flavors and aromas that reduce the quality of cocoa in the production of chocolate.